Analisis Perencanaan dan Kajian Ekonomi dalam Penggunaan PV Menuju Low Energy Building Pada Hote Inaya Putri Bali - Fendy Eventius Mugni; Bambang Widodo; Stepanus Stepanus (Prodi Teknik Elektro FT UKI, 2020)
Industrial and business growth develops rapidly from time to time. This also encourages higher energy use and energy use is a major contributor to operational costs. This study aims to carry out planning and economic studies in the use of PV towards a low-energy building at Hote Inaya Putri Bali. The method used in this research is the survey method and literature study. Primary data is obtained from the 2019 Electricity Bill. The data is then used to calculate the Intensity of Energy Consumption, then taken from energy simulations using solar solar with Homer software simulations. The results showed that the IKE in the Inaya Putri Bali Hotel building was 131.8 kWh / m2 / year, meaning that energy use in the Inaya Putri Bali Hotel building was still efficient. Using the solar cell simulation results, the energy obtained is 443,732 kWh per year at a cost of Rp. 972 / kWh, which means energy savings of Rp. 35,942,292 per month or 14.5% per year.